Gamified Vocabulary Learning in Vocational EFL Contexts: A Longitudinal Mixed-Methods Study of Motivation, Anxiety, and Lexical Gains - Turki Alsolami (Journal of Education, Pedagogy and Teacher Training, 2026)
Gamification has attracted sustained interest in EFL pedagogy as a strategy for increasing learner engagement and reducing the affective barriers that often accompany vocabulary learning. Yet most studies have examined gamified vocabulary instruction in general secondary or university settings, leaving vocational EFL contexts where learners typically have specific occupational language goals, constrained instructional time, and varied prior exposure to English underrepresented in the research. This study investigates the effects of gamified vocabulary learning on motivation, foreign language anxiety, and lexical gains among vocational high school students in Aceh, Indonesia, over fourteen weeks. Using a mixed-methods sequential explanatory design, the study combines pre- and post-test vocabulary measures, Foreign Language Anxiety Scale scores, and Intrinsic Motivation Inventory ratings with qualitative data from semi-structured interviews and classroom observations. Findings indicate significant gains in vocabulary breadth and retention for the gamified group compared to a control group receiving conventional instruction, alongside reductions in anxiety and increases in intrinsic motivation. Qualitative data complicate this broadly positive picture, however, revealing that gamification's motivational effects were uneven: competitive elements energised high-achieving students while quietly increasing the anxiety of lower-confidence learners. The study draws on Self-Determination Theory (Deci & Ryan, 2000; Ryan & Deci, 2020) and Complexity Theory perspectives on language learning (Larsen-Freeman & Cameron, 2008) to argue that effective gamified vocabulary instruction in vocational EFL contexts requires careful attention to how competition, collaboration, and learner identity intersect in the specific cultural and institutional conditions of each classroom.